Monilethrix - Improvement with acitretin - Karincaoglu, Y; Coskun, BK; Seyhan, ME; Bayram, N (Adis Int Ltd, 2005)
Monilethrix is a rare hereditary disorder that affects the hair and is characterized by shaft anomaly. There is no known treatment that successfully cures the condition. In this report we present a case of monilethrix in a 7-year-old girl treated with oral acitretin. A very good clinical and cosmetic result was obtained while treatment was continued. However, clinical symptoms recurred after discontinuation of acitretin therapy.
Keywords: Etretinate Therapy; Children; Keratinization; Disorders; Retinoids